2018
DOI: 10.2147/ppa.s171533
|View full text |Cite
|
Sign up to set email alerts
|

Women’s cesarean section preferences and influencing factors in relation to China’s two-child policy: a cross-sectional study

Abstract: ObjectiveThis study explored women’s preference for cesarean section (CS) and the preference for cesarean sections’ influencing factors, particularly nonmedical factors.MethodsA cross-sectional study was conducted in four tertiary hospitals in Hohhot. We recruited 1,169 pregnant women at ≥ 28 gestational weeks and classified subjects into three groups by delivery mode preference: vaginal birth (VB), CS, and “no clear preference”. We identified the influencing factors of women’s choices by multinomial logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 24 publications
1
19
1
3
Order By: Relevance
“…In this study majority of the women in Bangladesh preferred NVD and whereas only one in every fourteen women preferred CS, we also found the similar result in the other studies [7]; [24]; [25]. Almost four out of ten participants had no clear preference which is large comparing to the study conducted in China [26].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In this study majority of the women in Bangladesh preferred NVD and whereas only one in every fourteen women preferred CS, we also found the similar result in the other studies [7]; [24]; [25]. Almost four out of ten participants had no clear preference which is large comparing to the study conducted in China [26].…”
Section: Discussionsupporting
confidence: 86%
“…The result of logistic regression showed that mother's age has a significant effect on CS, however, a hospital-based study from china also showed higher CS rate for 40 years above old women [26]. Also, a population-based study from Taiwan reported that older than 34 years women were preferred CS for their child birth [27].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other researchers have identi ed from the clinician's point of view what factors in uence the decision to perform caesarean section and found these to be the clinician's personal beliefs, health care systems factors and clinician's characteristics which includes con dence, skills and convenience [12]. On the other hand, in patient-initiated caesarean section, women make this decision based on maternal and infantrelated factors, social in uences, the certainty about the timing of the delivery, choosing a lucky day for baby birth and unpleasant experiences with previous vaginal delivery [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al's retrospective cohort study demonstrated that trial of labour after caesarean delivery may be a potential strategy for decreasing the CSD rate [80]. This steady decline of CSD, particularly significant among nulliparous and multiparous births without a uterine scar, which is concomitant with a decline in perinatal mortality from 10.1 per 1,000 births to 7.2 per 1,000 births, is the result of institutional interventions and policy change [81]. While in Brazil, Galvao et al [82] propose the enforcement of Resolução Normativa 368, in addition to structural changes (e.g.…”
Section: Intercontinental Comparison Of Csd Outcomesmentioning
confidence: 99%